Implementation of the Need for Recovery of Economic Conditions After the Covid-19 Pandemic in Sumedang Regency - Shinta Rizqiya (Universitas Sebelas April, Fakultas Ekonomi dan Bisnis, 2022)
The purpose of this study is to describe and analyze the impact of the Covid-19 pandemic on the economic conditions of the Sumedang community. The study method uses qualitative descriptions that are rational, empirical, and systematic in explaining economic phenomena. Secondary data sources from the Central Statistics Agency of Sumedang, primary data from questionnaires. The population is residents aged 15 years and over who work based on business fields in Sumedang Regency in 2021. The determination of the sample is based on the Two Stage Cluster, the primary sample is 156.223 people, the sampling error assumption is 0.22%, the confidence coefficient assumption is 1.96 and Assuming the binomial proportion parameter of 50%-50%, a sample of 797 people was obtained. The research time is from March to November 2021 with locations in 9 (nine) sub-districts throughout Sumedang Regency. Collecting data by surveying the instrument in the form of an open questionnaire which is divided into two parts, an open administrative questionnaire and an open substantive questionnaire. The efforts made are expected to be in the informal sector so that their productivity can be increased, capacity and capacity building is needed both in the business field and the informal sector, infrastructure development that supports the use of technology and strengthening digital marketing with an online platform approach that is willing to synergize and protect employment with schemes. balanced. The Covid-19 pandemic has had an impact on job dynamics, distribution of government aid, scarcity of basic needs, income and shifts in business fields.